2018
DOI: 10.1186/s40535-018-0055-8
|View full text |Cite
|
Sign up to set email alerts
|

Concept embedding-based weighting scheme for biomedical text clustering and visualization

Abstract: Active research and practice in the medical domain has generated pervasive text files, articles, and documents, which include MEDLINE-the largest biomedical text database, clinical notes in the Electronic Health Records, descriptions of clinical trials, and so on. In order to efficiently discover, search, and access the knowledge within all these text content, there is a continuous need for developing innovative techniques and algorithms for text representation, clustering, and visualization. Within the biomed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, use of conventional and modern technology in document clustering analysis is essential in biomedical area. Luo and Shah presented a biomedical text clustering framework based on disease concepts in their study [41]. To accomplish this, they extracted disease phrases and then constructed concept embeddings using neural networks.…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, use of conventional and modern technology in document clustering analysis is essential in biomedical area. Luo and Shah presented a biomedical text clustering framework based on disease concepts in their study [41]. To accomplish this, they extracted disease phrases and then constructed concept embeddings using neural networks.…”
Section: Related Workmentioning
confidence: 99%
“…In more recent studies, a semantic weight is suggested to express domain relatedness between concepts in the medical domain. We can cite as an example the research work discussed in [26], where word embeddings of all medical concepts are extracted from a corpus of biomedical texts. Then, an association score between each pair of concepts is calculated so that the weight of a concept in a document corresponds to the addition of its TF-IDF frequency with the sum of the association scores of its co-occurring concepts highly associated with it.…”
Section: Related Workmentioning
confidence: 99%